Older people’s use of mobility aids in the built environment - ALLYSON ROGERS (2020)
The world population is ageing, by both number and share of older people (WHO 2013), leading to ageing issues being increasingly discussed within transport and mobility fields (Murray 2016; Schwanen & Paez, 2010). As those over 70 are the group most likely to have mobility and accessibility issues, there is a need to look at the wider relationship between mobility and ageing in relation to health and well-being (Musselwhite 2016). The social model of disability and resulting accessibility legislation has heralded a great deal of improvement for the inclusion of those with disabilities, but there seems to be little attention paid to emotional or psychological needs of people with physical impairments (Oliver, 2013), or disability and mobility aid use by older people (Jönson & Taghizadeh Larsson, 2009; Minkler & Fadem, 2002; Phillips, Ajrouch, & Hillcoat-Nallétamby, 2010; Raymond, Grenier, & Hanley, 2014). From the perspective of mobility aid provision, outcomes are measured in terms of independence for user, without considering the impact of this functionality on mobility aid user or carer, family or social life (Hammel et al, 2013). This study has taken an ethnographic grounded theory approach using observation, sound recording, photography, storytelling and discussion as methods for data collection. People who use mobility aids (n=11) were recruited to give accounts of mobility aid use during daily routine activities, along with the accounts of some of their family members and carers (n=6). Constant comparative analysis through coding and revisiting the field on an iterative basis was employed to describe and begin to understand mobility aid use by older people in the built environment. A complex and interlinking array of experiences and obstacles to inclusion was found for this group of people on individual, relational and infrastructural levels, with themes of identity, relationships and infrastructure and interlinking systems emerging from the data. The findings contribute information regarding a complex relationship between mobility aid use and ageing. The impact of reduced mobility and mobility aid use on identity and relationships is exacerbated by ineffective or inconsistent policies and systems. Social, psychological, emotional and physical costs of unequal access are being met by older mobility aid users and their carers. The implications of these findings are that this area requires more attention from both research and policy and planning arenas to ensure older people who use mobility aids are appropriately accommodated in the built environment. Policy and planning are found to not consistently provide a cohesively supportive environment for older people who use mobility aids to effectively participate socially.